Potential of Genomic Selection for Mass Selection Breeding in Annual Allogamous Crops. Issue 1 (1st January 2013) - Yabe, Shiori; Ohsawa, Ryo; Iwata, Hiroyoshi
Abstract : Mass selection is an important method for genetic improvement of allogamous crops. It is nevertheless inefficient mainly because of the inaccuracy of single‐plant evaluation. Genomic selection (GS) based on whole‐genome markers might improve mass selection efficiency. Our objective was to assess the potential of mass selection with GS for the genetic improvement of an annual allogamous crop population under various conditions. Allogamous crops often have low levels of linkage disequilibrium. Therefore, we assumed linkage equilibrium in an initial breeding population and conducted simulations to compare GS with phenotypic selection (PS) and conventional marker‐assisted selection (MAS) and to evaluate the impact of changing various features of GS breeding. We also evaluated the genetic gain per unit cost for GS and PS breeding. Results show that GS resulted in higher genetic gain than either PS or MAS. The mode of inheritance of markers made only a small difference. Genomic selection with a larger population size and more cycles attained higher genetic gain except when the population size was as small as 50. The cost efficiency of GS was higher than that of PS with identical population size when the genotyping cost was lower than about one‐fourth of the phenotyping cost. Genotyping costs are decreasing rapidly. Therefore, GS is anticipated as an important breeding method to support mass selection of allogamous crops.